Three new combinations in the genus Phanera (Fabaceae: Cercidoideae) including the lectotypification of Bauhinia strychnifolia - Jiang, Kai-Wen; Gu, Shi-Ran; Li, Shi-Jin; Tu, Tie-Yao; Zhang, Dian-Xiang (Phytotaxa, 2023)
Three new combinations in the genus Phanera are here proposed for the species originally placed in Bauhinia s. l., in which we also designate a lectotype for the name Bauhinia strychnifolia Craib.